2005
DOI: 10.1681/asn.2004080658
|View full text |Cite
|
Sign up to set email alerts
|

Urine Chemokines as Biomarkers of Human Systemic Lupus Erythematosus Activity

Abstract: The purpose of this study was to evaluate urine monocyte chemoattractant protein-1 (MCP-1) and IL-8 as biomarkers of SLE flare. Urine was collected every 2 mo from patients who were followed prospectively in the Ohio SLE Study. Renal and nonrenal flares were identified and MCP-1 and IL-8 were measured by specific ELISA in samples that were collected at flare. When available, MCP-1 and IL-8 were also measured in urine samples before and after flare. For comparison, MCP-1 and IL-8 were measured in the urine of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
215
3
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 240 publications
(238 citation statements)
references
References 23 publications
17
215
3
3
Order By: Relevance
“…Several more recent studies, both cross-sectional and longitudinal, have confirmed those findings [Kiani et al 2009;Rovin et al 2005;Tian et al 2007;Tucci et al 2004]. For example, in a study conducted by Rovin and colleagues [Rovin et al 2005], it was shown that uMCP-1 level was a sensitive indicator for renal flare, with 73% of the uMCP-1 levels measured at renal flares higher than the 95th percentile of the disease controls. uMCP-1 levels did not correlate with extrarenal disease activity.…”
Section: Complementmentioning
confidence: 74%
“…Several more recent studies, both cross-sectional and longitudinal, have confirmed those findings [Kiani et al 2009;Rovin et al 2005;Tian et al 2007;Tucci et al 2004]. For example, in a study conducted by Rovin and colleagues [Rovin et al 2005], it was shown that uMCP-1 level was a sensitive indicator for renal flare, with 73% of the uMCP-1 levels measured at renal flares higher than the 95th percentile of the disease controls. uMCP-1 levels did not correlate with extrarenal disease activity.…”
Section: Complementmentioning
confidence: 74%
“…Tubulointerstitial fibrosis involving less than 10% of the renal cortex was considered mild, fibrosis involving between 10% and 25% of the cortex was considered moderate, and fibrosis involving over 25% of the cortex was considered severe. Urine MCP-1 was measured by specific ELISA as we have described previously (38). Urine TGF-β was also measured by specific ELISA obtained from R&D Systems.…”
Section: Resultsmentioning
confidence: 99%
“…The OSS has been described previously (11,12). Patients in the OSS were followed from 2001 to 2009, with a median duration of follow-up of 6 years.…”
Section: Methodsmentioning
confidence: 99%
“…The specific changes of disease activity (proteinuria, SCr, and urine sediment) required to diagnose a flare have been previously published (11). In the OSS, flares were divided into mild, moderate, and severe, and specific treatment guidelines were applied to each level of flare (11,12). Flares were not divided into nephritic and proteinuric, and treatment was not based on the nephritic/ proteinuric designation.…”
Section: Definition Of Renal Flarementioning
confidence: 99%
See 1 more Smart Citation